Pengaruh Intensitas Penggunaan Media Sosial, Motivasi Belajar, Dan Manajemen Waktu Terhadap Prokratinasi Akademik Siswa SMKN 25 Jakarta - Nadila Nur Latifah; Corry Yohana; Annisa Lutfia (Universitas Pahlawan Tuanku Tambusai, 2023)
This is a quantitative-research aimed to examine the influence of social media usage intensity, learning motivation, and time management on academic procrastination. The study involved a sample of 188 students from X and XI grades at SMKN 25 Jakarta, selected using proportional random sampling based on the Slovin formula. The data were analyzed using the SEM-PLS method with Smart PLS 4.0 software. The main objective of this research is to identify the effects of independent and dependent variables, both individually and collectively. To test these relationships, coefficient of determination, t-test, and F-test methods were used. The results of the hypothesis testing revealed that: (1) Intensity of Social Media Usage has a positive and significant effect on Academic Procrastination, (2) Learning Motivation has a negative and significant effect on Academic Procrastination, (3) Time Management has a negative and significant effect on Academic Procrastination, and (4) Collectively, Intensity of Social Media Usage, Learning Motivation, and Time Management have a significant impact on Academic Procrastination. Keywords: intensity of social media use, learning motivation, time management, academic procrastination